STUDI KASUS PEMERIKSAAN RADIOGRAFI KNEE JOINT DENGAN KLINIS OSTEOARTHRITIS DI INSTALASI RADIOLOGI RS ORTHOPEDHI PROF.DR.SOEHARSO SURAKARTA - Risaldi Derheman,; Ayu Mahanani,; Retno Wati, (Journal of Innovation Research and Knowledge, 2025)
Introduction: Radiographic examination of the knee joint is performed to evaluate the condition of the knee joint, including cartilage and surrounding soft tissues. At Prof. Dr. Soeharso Orthopedic Hospital Surakarta, examinations for osteoarthritis cases utilize anteroposterior (AP) and lateral projections, with an additional lateral flexion-extension projection. This approach differs from theoretical standards, which recommend AP, AP oblique, lateral, and AP/PA weight-bearing projections as additional views. Method: This research is a case study employing a qualitative descriptive approach. It was conducted at the Radiology Installation of Prof. Dr. Soeharso Orthopedic Hospital Surakarta from May to June 2025. Subjects included three radiographers and one radiology specialist physician, with the research objects comprising knee joint examinations in patients with osteoarthritis. Data were collected through observation, interviews, documentation, and literature review. Data analysis involved reduction, presentation via coding graphs, and conclusion drawing. The study obtained Ethical Clearance No: PP.01.03/D.XXV.2/3897/2025. Results: Knee joint examinations required no special preparation, except for the removal of metallic objects such as knee braces. The projections used include AP, lateral, and additional lateral flexionextension in the supine position, utilizing a 35x43 cm cassette, centering point at the midpoint of the knee, and FFD of 100 cm. The lateral flexion-extension projection aimed to assess joint flexibility and ligament conditions (ACL and PCL), which were crucial for determining orthopedic interventions such as total knee replacement (TKR) or high tibial osteotomy (HTO). Conclusion: The lateral flexion-extension projection is beneficial for evaluating joint flexibility and ligament integrity, serving as a valuable supplementary reference in radiographic examinations of the knee joint for osteoarthritis